PENGARUH KESELAMATAN DAN KENYAMANAN KERJA TERHADAP PENCAPAIAN TARGET KERJA DIVISI PRODUKSI PADA PT WASKITA BETON PRECAST, TBK PLANT GASING PALEMBANG - Ari Widianto; Akila Akila; Mursalin Mursalin (Universitas Nusa Cendana, 2023)
This review aims to test the impact of Working Safety and Working Comfort on the Achievement of Working Targets in the production division at PT Waskita Beton Precast, Tbk Plant Gasing Palembang. The technique utilized in this study is a quantitative strategy. The strategy was utilized to examine the sample of 36 respondents. The data were analyzed to obtain the correlation coefficient and coefficient of determination. t-test, and F test with the SPSS for Windows 22 aims to test the hypotheses. The findings imply that there is a significant impact of Working Safety on the Achievement of Working Targets. While the variable of Working Comfort has an impact on the Achievement of Working Targets. It may be inferred that there is a significant impact between Working Safety and Working Comfort on the Achievement of Working Targets in the production division at PT Waskita Beton Precast, Tbk Plant Gasing Palembang. Keywords: Working Safety; Working Comfort; Achievement of Working Targets